Experiences of Nursing Students Regarding Challenges and Support for Resilience during Clinical Education: A Qualitative Study - Aryuwat, Pimwalunn; Holmgren, Jessica; Asp, Margareta; Radabutr, Matanee; Lövenmark, Annica (Nursing reports (Pavia, Italy), 2024)
Nursing students require resilience to navigate the complexities of clinical practice. This characteristic is essential for managing demanding workloads, unpredictable patient situations, and emotional stressors while maintaining performance and well-being. Fostering resilience helps students develop the capacity to adapt to adversity, overcome setbacks, and remain committed to providing high-quality patient care. This qualitative study explores the challenges and supports influencing nursing students’ resilience during clinical education. Interviews with 28 Thai nursing students revealed two key themes: the “experience of vulnerability” and the “experience of meaningfulness”. The sub-themes of vulnerability included “navigating uncertainty”, “transcending professional struggles”, and “being exposed to diverse encounters”. The sub-themes of meaningfulness focused on restoring strength through social interactions and engaging in positive transformation. This study highlights the need for comprehensive support systems that address personal and professional vulnerabilities. Integrating caring theory principles could further enhance resilience by emphasizing compassionate care and fostering student empathy. This suggests that instructors and stakeholders can significantly impact student well-being by creating supportive environments built on collaboration, empathy, and mentorship, all of which are aligned with caring theory.